Study of mechanical and wear characteristics of AL380 composite fabricated by introducing B4C using compo casting method - V. M. Prasad, Ch.; Mallikarjuna Rao, K. (International Journal of Engineering and Technology, 2018)
In the present work, Al380 Al alloy and B4C metal matrix composite was fabricated with different weight fractions (1%,2% and 3%) using compo-casting method. The wear properties of fabricated composite is tested by pin on disc apparatus. On different loads of 30N,60N and 90N the wear tests are performed. The mechanical properties of hardness and tensile strength are performed on brinell’s hardness apparatus and Ultimate tensile machine. The study of homogeneous distribution of B4C particles were examined by scanning electron microscope (SEM) in the composites. The result shows that the Al380 Al alloy reinforced with B4C particles, that composite improves the mechanical properties and wear rate. Increasing of wear rate with the increase in B4C particles in composites. Using Opti- cal microscope, the study of worn surfaces of pins were analyzed.